Dementia-friendly prisons: a mixed-methods evaluation of the application of dementia-friendly community principles to two prisons in England - Tine Van Bortel; Samantha Treacy; Anna Haggith (BMJ Open)
Objectives To apply and evaluate dementia-friendly community (DFC) principles in prisons.Design A pilot study and process evaluation using mixed methods, with a 1-year follow-up evaluation period.Setting Two male prisons: a category C sex offender prison (prison A) and a local prison (prison B).Participants 68 participants—50 prisoners, 18 staff.Intervention The delivery of dementia information sessions, and the formulation and implementation of dementia-friendly prison action plans.Measures Study-specific questionnaires; Alzheimer’s Society DFC criteria; semi-structured interview and focus group schedules.Results Both prisons hosted dementia information sessions which resulted in statistically significant (p>0.05) increases in attendees’ dementia knowledge, sustained across the follow-up period. Only prison A formulated and implemented a dementia action plan, although a prison B prisoner dedicated the prisoner magazine to dementia, post-information session. Prison A participants reported some progress on awareness raising, environmental change and support to prisoners with dementia in maintaining independence. The meeting of other dementia-friendly aims was less apparent. Numbers of older prisoners, and those diagnosed with dementia, appeared to have the greatest impact on engagement with DFC principles, as did the existence of specialist wings for older prisoners or those with additional care needs. Other barriers and facilitators included aspects of the prison institution and environment, staff teams, prisoners, prison culture and external factors.Conclusions DFC principles appear to be acceptable to prisons with some promising progress and results found. However, a lack of government funding and strategy to focus action around the escalating numbers of older prisoners and those living with dementia appears to contribute to a context where interventions targeted at this highly vulnerable group can be deprioritised. A more robust evaluation of this intervention on a larger scale over a longer period of time would be useful to assess its utility further.